Validation of void fraction models and correlations using a flow pattern transition mechanism model in relation to the identification of annular vertical downflow in-tube condensation of R134a - Dalkilic, A. S.; Wongwises, S. (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
This paper reports the experimental investigation of a model for predicting flow pattern transitions and for the validation of void fraction models and correlations proposed in the authors' previous publications and for the identification of flow regimes in data corresponding to annular flow downward condensation of R134a in a vertical smooth copper tube having an inner diameter of 8.1 mm and a length of 500 mm. R134a and water are used as working fluids on the tube side and annular side, respectively, of a double tube heat exchanger. Condensation experiments are done at mass fluxes of 260 and 515 kg m(-2) s(-1) in the high mass flux region of R134a. The condensing temperatures are between 40 and 50 degrees C; heat fluxes are between 10.16 and 66.61 kW m(-2). A mathematical model proposed by Soliman based on the models of Kosky and Lockhart-Martinelli is used to determine the condensation film thickness of R134a. Comparative void fraction values are determined indirectly using the measured data under laminar and turbulent flow conditions together with various void fraction models and correlations reported in the literature. There is good agreement between the void fraction results obtained from the theoretical model and those obtained from the void fraction models of Soliman, Chisholm and Armand, Turner and Wallis, Smith, Spedding and Spence previously proposed in the authors' publications and tested against their experimental database. Various well-known flow regime correlations from the literature are investigated to identify the flow regime occurring in the test tube, the correlations of Taitel and Dukler, Dobson, Akbar et al., Breber et al., Cavallini et al., and Sardesai et al. can provide accurate estimates of the annular flow conditions in spite of their different working conditions. (C) 2010 Published by Elsevier Ltd.
Keywords: Condensation; Flow regime map; Vertical down flow; R134a; Phase change; HEAT-TRANSFER COEFFICIENT; 2-PHASE FRICTION FACTOR; HIGH-MASS FLUX; SMOOTH TUBE; HORIZONTAL TUBES; DOWNWARD FLOW; REGIMES; MICROCHANNELS; MAP; Thermodynamics; Mechanics